Numerial methods of solution of boundary-value problem for differential-algebraic equations ofsecond order - Bulatov, Mikhail Valeryanovich (Trường Đại học Đà Lạt, 2012)
In this paper, some numerical methods for solving differential-algebraic equations of the second order are considered. We give conditions under which the algorithms are stable and converge to tbe exact solution of tbe original problem. Numerical examples are given. Mathematics Subject Classification. 65R20, 45F15.